2021
DOI: 10.3389/fimmu.2021.663726
|View full text |Cite
|
Sign up to set email alerts
|

MiR-154-5p-MCP1 Axis Regulates Allergic Inflammation by Mediating Cellular Interactions

Abstract: In a previous study, we have demonstrated that p62, a selective receptor of autophagy, can regulate allergic inflammation. In the present study, microRNA array analysis showed that miR-154-5p was increased by antigen (DNP-HSA) in a p62-dependent manner in rat basophilic leukemia cells (RBL2H3). NF-kB directly increased the expression of miR-154-5p. miR-154-5p mediated in vivo allergic reactions, including passive cutaneous anaphylaxis and passive systemic anaphylaxis. Cytokine array analysis showed that antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…In addition, they can act as transporters of different miRNAs, which exert their action on the target cell [226]. Precisely, two of them have been characterized in anaphylaxis, miR-135-5p and miR-154-5p, which can regulate allergic inflammation in a p62 protein-dependent manner [179,227].…”
Section: Communication Between Microenvironments: Mirnas and Evsmentioning
confidence: 99%
“…In addition, they can act as transporters of different miRNAs, which exert their action on the target cell [226]. Precisely, two of them have been characterized in anaphylaxis, miR-135-5p and miR-154-5p, which can regulate allergic inflammation in a p62 protein-dependent manner [179,227].…”
Section: Communication Between Microenvironments: Mirnas and Evsmentioning
confidence: 99%
“…Only three miRNAs, such as miR-154, miR-377, and miR-885-5p, were not retrieved in previous analysis [ 81 ]. However, based on recent literature, all of them are related to NF-kB/inflammation pathways [ 82 , 83 , 84 ]. All of the 68 NF-kB responsive miRNAs are therefore included in the Venn diagram reported in panel B, highlighting that these miRNAs identified as tissues expressed miRNAs are also detectable in blood, and most of them were identified inside extracellular vesicles, i.e., exosomes (miRNAs depicted in inner circles Figure 7 B).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that miR-154-5p is able to reverse a circ-Scmh1-induced microglial polarisation from M1 to M2 via STAT6 binding [ 23 ], which may alter TLR7 signalling [ 46 ]. Also, miR-154-5p seems to be involved in allergic inflammation mediated by MCP-1 [ 47 ]. Although we determined some cytokines in addition to TNF at the mRNA level produced in response to miR-154-5p, an in-depth characterisation of the cytokine/chemokine pattern released from microglia responding to miR-154-5p would be valuable to fully understand the interaction between miR-154-5p and TLR7 as well as the cellular consequences of such an interaction, especially in human and disease contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Although we determined some cytokines in addition to TNF at the mRNA level produced in response to miR-154-5p, an in-depth characterisation of the cytokine/chemokine pattern released from microglia responding to miR-154-5p would be valuable to fully understand the interaction between miR-154-5p and TLR7 as well as the cellular consequences of such an interaction, especially in human and disease contexts. Also, further research is required to characterise the role of miR-154-5p in inducing a microglial M1 and/or M2 state and to assess whether TLR signalling and further signalling cascades, such as MCP-1, which miR-154-5p is considered to regulate [ 47 ], are involved in these processes. Finally, the alteration of some signalling components, but not others such as MYD88 and TRIF, is of interest.…”
Section: Discussionmentioning
confidence: 99%